Lipases immobilized on the modified polyporous magnetic cellulose support as an efficient and recyclable catalyst for biodiesel production from Yellow horn seed oil. (January 2020) - Zhang, Huaxia; Liu, Tianshu; Zhu, Yawei; Hong, Li; Li, Tianfeng; Wang, Xiqing; Fu, Yujie
Abstract: In the present study, modified polyporous magnetic cellulose beads (PMCBs) were synthesized by several organic amines (EDA, DETA, TETA and AST) grafting PMCBs and then utilized as a new kind of support to immobilize Candida antarctica lipase B (CALB) for biodiesel production. The immobilized lipase catalysts based on PMCBs were characterized by Fourier transform infrared and scanning electron microscopy. The results showed that PMCBs-DETA was a more suitable immobilization support and the catalytic activity of immobilized lipases could reach 1.0 U/mg. Then the synthesized catalyst of CALB-PMCBs-DETA was used to produce biodiesel from Yellow horn seed oil via transesterification reaction. A high biodiesel yield (92.3%) was obtained under the optimal reaction conditions and the main compositions of the prepared biodiesel were tested by GC-MS. Moreover, the catalyst of CALB-PMCBs-DETA could be removed easily by a magnet and recycled at least 5 times. As a new kind of support, the modified PMCBs could be a promising alternative for the carriers of immobilizing enzymes used for the green and efficient production of biodiesel. Graphical abstract: Image 1079 Highlights: PMCBs were modified by grafting amines and CALB was immobilized on the modified support materials for the first time. The synthesized catalyst of CALB-PMCBs-DETA could be removed from the reaction system easily by a magnet. This study provide a promising alternative for the carriers of immobilizing enzymes.